A Theorem on the Commutative Neutrix Product of Distributions - Fisher, Brian; Öz¸ça, E.; Gülen, Ü. (Sarajevo Journal of Mathematics, 2024)
The commutative neutrix products $f_+(x) · δ ^{(r)}(x)$ and $f_-(x)$ $· δ ^{(r)}(x) $ are evaluated for $r=0,1,2,…,$ where $f$ is a function which is infinitely differentiable on an open interval containing the origin and $f_+(x) =H(x)f(x)$ and $f_-(x) =H(-x)f(x),$ $H$ denoting Heaviside's function. 2000 Mathematics Subject Classification. 46F10